PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN TOTAL ASSETS TURNOVER TERHADAP RETURN ON EQUITY (Studi Empiris pada Perusahaan Publik Sub Sektor Advertising, Printing, dan Media di Bursa Efek Indonesia Periode 2015-2019) - Ivo Rolanda; Mia Laksmiwati (Jurnal Ekonomika dan Manajemen, 2022)
This study aims to determine the effect of Current Ratio on Return On Equity, Debt to Equity Ratio on Return On Equity, and Total Asset Turnover on Return On Equity ln the Advertising, Printing, and Media sub-sectors listed on the Indonesia Stock Exchange for the period 2015–2019. The sample of this study was determined using the purposive sampling method so that 15 companies were selected ln the Advertising, Printing, and Media sub-sectors that were listed on the Indonesia Stock Exchange for the 2015-2019 period. This study was conducted using multiple linear regression methods assisted by SPSS version 22.0 and Microsoft Excel 2016. The results showed that Current Ratio, Debt to Equity and Total Asset Turnover had an effect on Return On Equity.